The Historical Emergence of Shi‘ism and Its Development in the Islamic World - R, Rismayani; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study of Shi‘ism is essential, as its existence encompasses not only historical and political dimensions but also influences the dynamics of inter-sectarian relations within the Islamic world. A comprehensive understanding of the history and development of Shi‘ism is expected to enrich Islamic discourse and foster tolerance among Muslims. This research employs a library research method, utilizing various written sources to collect relevant data and information. The collected data were analyzed qualitatively. The findings reveal that the peak of Shi‘a development occurred during the medieval period when the Safavid dynasty established Shi‘ism as the official school of thought in Iran. Its influence further expanded following the 1979 Islamic Revolution, which inspired a broader revival of Islamic consciousness worldwide. To this day, Shi‘ism remains an integral part of the Muslim community, with followers distributed across various regions. Although differences between Sunni and Shi‘a groups continue to cause tension in some areas, ongoing efforts in dialogue and the spirit of ukhuwah Islamiyah (Islamic brotherhood) are continuously promoted to foster unity among Muslims on the basis of faith and humanity.